Issues and Strategies for Group and Negotiation Support Systems Research - Pervan, Graham; Arnott, D. (IGI Global, 2014)
This research project was principally motivated by a concern for the direction and relevance of research in systems that support group work and negotiation. The main areas of research focus are the publication frequency and outlets for GSS and NSS research, the research strategies used in published articles, and the professional relevance of the research. The project has analysed 383 GSS articles and 82 NSS articles published in 16 major journals from 1990 to 2010. The findings indicate a significant dependence on the Journal of Group Decision and Negotiation but represent an opportunity for newer journals such as the International Journal of Decision Support Systems Technology. Other issues include a focus on experimental research and design science, weak theoretical foundations and research methodologies, and a focus on operational level problems.Of great concern is the finding that GSS and NSS research has relatively low professional and managerial relevance. Eight key strategies for dealing with these issues are recommended.